EFFICACY OF DIFFERENT TYPES OF TREATMENT OF CEPHALGIA IN CHILDREN AND ADOLESCENTS WITH ARTERIAL HYPERTENSION - A.N. Rakhimova; V.I. Tambovtseva; A.E. Pal'zeva; V.V. Vasil'chenko; O.V. Kozhevnikova (Педиатрическая фармакология, 2010)
Examined was the efficacy of integrated therapy for cephalgia syndrome in 201 children aged 7 to 17 years with various forms of arterial hypertension through daily monitoring of arterial pressure and transcranial dopplerography of brain vessels. Treatment was performed in courses over 3 years. Results were assessed at 1,5 and 3 years from the launch of treatment. Tactics were determined for treating cephalgia syndrome in children and adolescents depending of the form of arterial hypertension and specifics and cerebral hemodynamics. Key words: cephalgia, arterial hypertension, daily monitoring of arterial pressure, transcranial dopplegraphy, disorders of the vegetative nervous system, children. (Pediatric Pharmacology. – 2010; 7(4):72-80)